(untitled) (Innovation & Development in Engineering and Applied Science, 2025)
The present research reviews the impact of educational robotics on the development of competencies of students in Ecuador. In a context where education seeks to adapt to the demands of the 21st century, robotics is presented as an innovative tool to improve learning. The objective of this review is to analyze how the implementation of robotics in the classroom contributes to the development of technical and soft skills. A documentary methodology was used, reviewing previous studies and educational experiences in different institutions. The analysis techniques included literature review and case study. The main results indicate that students participating in educational robotics activities improved significantly in areas such as problem solving, teamwork and creativity [2]. In addition, an increase in motivation and interest in core subjects was observed. In conclusion, educational robotics not only enhances the learning of technical skills, but also fosters interpersonal skills, preparing students to face the challenges of future employment in an increasingly technological world.